Penerapan Model Pembelajaran RADEC untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Pada Materi Fluida Dinamis - Septian, Akmal; Muslim; Danawan, Agus (Unnes Physics Education Journal, 2025)
This study aims to examine the effectiveness of the application of the RADEC learning model in improving students' critical thinking skills on dynamic fluid material. The method used is a quantitative approach with a quasi-experimental design in the form of a non-equivalent control group design. The research sample consisted of 24 students in class XI at Bunga Bangsa High School, Bandung City, who were selected using sampling purposive technique. The research test instrument was 18 multiple choice questions to measure critical thinking skills. Data were analyzed using N-Gain calculation, and effect size. The results showed that there was an increase in critical thinking skills in students who were treated with the RADEC learning model. After treatment with the RADEC learning model, the results found the N-Gain value of 0,62 which is in the medium category. The RADEC learning model is proven to have a positive impact on improving students' critical thinking skills with an effect size of 2,447 in the very high category.